Maisbich (Luxemburg) temperature data, sensor 1239546_coolbox, month 2009-05 - W.M.J.(Wim) Luxemburg; M.C.(Martijn) Westhoff (4TU.Centre for Research Data, 2011)
Parent item:
Maisbich (Luxemburg) temperature data, sensor 1239546_coolbox
Measuring instrument:
Temperature sensor 1239546_coolbox, Maisbich (Luxemburg)
Temperature sensor,TidbiT v2 temp logger: Hobo USA.
Temperature of water in a box. In the same box ca 30 m of DTS fiber optic cable measues temperature.
Keywords: Physical Geography and Environmental Geoscience; Collection: Darelux - River Environment Luxemburg; climate; hydrology; river basin; water temperature; Time: 2009-05